Introduction to the Special Issue on Police Legitimacy with a Focus on Ethnic–Racial Minorities - Cao, Liqun (Canadian journal of criminology and criminal justice, 2022)
This special issue examines the study of legitimacy with a focus on racial-ethnic minority relationships in criminal justice system. The violent and senseless death of George Floyd in the United States on 25 May 2020 has galvanized the recent international Black Lives Matter movement and represented one of the many tragedies in the history of the global racialized criminal justice system, Canada included. The criminal justice system of Canada has a disturbing and problematic history of oppression and colonialism. Against this historical backdrop, however, Canada has been able to develop its own research on a number of key themes, voice these concerns on scientific grounds, and pave its own way towards a more inclusive multicultural future. The special issue is part of the efforts during the extraordinary circumstances of the Covid-19 pandemic, which witnessed a short invocation of police emergency powers in Ottawa.